FRI0576 Economic Impact of Lower-Limb Osteoarthritis Worldwide: A Systematic Review of Cost-of-Illness Studies. (15th July 2016) - Salmon, J.H.; Rat, A.C.; Sellam, J.; Michel, M.; Eschard, J.P.; Guillemin, F.; Jolly, D.; Fautrel, B.
Abstract : Background: Lower limb osteoarthritis (OA) is an expanding public health problem owing to the aging of the population and increase in obesity prevalence. Knowledge of the economic burden is limited. Objectives: An overview of the economic consequences – overall costs as well as cost breakdown (direct and indirect) – of hip and knee osteoarthritis (OA) worldwide. Methods: A systematic literature search of EMBASE, MEDLINE, Scopus and Cochrane databases for articles was performed independently by 2 rheumatologists who used the same predefined eligible criteria. Papers without abstracts and in languages other than English or French were excluded. Extracted costs were converted to an annual cost and to 2013 euros (€) by using the Consumer Price Index of the relevant countries and the 2013 Purchasing Power Parities between these countries and the European Union average. Results: A total of 45 abstracts were selected, and 32 articles were considered for the review. The studiedpopulations were heterogeneous: administrative, hospital and national health survey data. Annual total costs per patient ranged from 0.7 to 12 k€, direct costs per patient from 0.5 to 10.9 k€ and indirect costs per patient from 0.2 to 12.3 k€. The weighted average annual costs per patient living with knee and hip OA were 11.1, 9.5 and 4.4 k€ for total, direct and indirect costs, respectively. Conclusions: This review highlights the heterogeneity of studies and lack of methodologic consensus to obtain reliable cost-of-illness estimates for lower-limb OA. However, costs induced by the disease seem substantial and deserve to be more extensively explored. Disclosure of Interest: None declared